The Moderating Role of Job Autonomy in the Relationship between the Use of Performance Appraisals and Job Satisfaction - Christian Grund; Anna Nießen (Institute of Labor Economics (IZA), 2025)
We explore the moderating role of job autonomy for the link between the use of performance appraisals and employees' job satisfaction. Results based on German linked employer-employee panel data show that performance appraisals are linked to higher job satisfaction at moderate levels of job autonomy, whereas this positive relationship weakens at both low and high levels of autonomy. Moreover, the interplay between performance appraisals and job autonomy appears sensitive to broader institutional and contextual factors, such as the existence of employee representation, perceived job security, and design of the performance appraisals. Our findings highlight the complex role of job autonomy in shaping employee responses to performance management, underscoring the need for context-aware human resource practices.
Keywords: M12; M5; J28; 330; job autonomy; performance appraisals; job satisfaction; German Linked Personnel Panel